Islamic Religious Education in Indonesia: Roles, Implementation, and Methods in Shaping Islamic Character in the Modern Era - Muhammad Yusuf Pratama; Ahmad Nabil Annuha; Ahmad Farid Fanani; Muhammad Azlan Lubis (Indonesian Journal of Islamic Educational Review, 2025)
The phenomenon of moral degradation among Indonesia’s young generation is increasingly alarming, marked by rampant deviant behavior, misuse of digital technology, and rising intolerance within educational settings. This situation demands strategic efforts to build Islamic character that remains relevant to the challenges of the modern era. This study aims to analyze the role, implementation, and instructional methods of Islamic Religious Education (PAI) in shaping students’ Islamic character, while identifying best practices for adaptation. Employing a qualitative approach through literature and field studies, data were collected via in-depth interviews, observations, and analysis of curriculum documents and learning modules. The findings reveal that PAI plays a central role in moral development by integrating the values of faith, piety, and noble character, supported by innovative methods such as cooperative learning, problem-based learning, gamification, and blended learning. Family and community involvement strengthen value internalization, while integrating Islamic digital literacy ensures PAI remains relevant amid globalization. These findings affirm that PAI is not merely a school subject, but the front line in safeguarding the nation’s moral integrity.